BRS Progresso - Rye cultivar - Nascimento Junior,Alfredo do (2014)
The rye cultivar BRS Progresso, developed by the Brazilian AgriculturalResearch Corporation (Embrapa), is the result of a synthetic cross of 18open-pollinated, self-incompatible lines, resistant to stem rust.